Perspektif Hukum Kebendaan dan Hak Kekayaan Intelektual dalam Menguji Legalitas NFT sebagai Objek Jaminan Kebendaan - Anastasya Maylan Anggraini; Aldira Mara Ditta Caesar Purwanto (Jurnal Hukum Lex Generalis, 2025)
This paper investigates the legal recognition of Non-Fungible Tokens (NFTs) as transferable assets and enforceable collateral in Indonesia’s civil legal system. The significance of this study arises from the substantial capitalization of NFTs, exemplified by Karafuru's valuation of IDR 1.2 trillion (2024) and other collections valued at 30 Ethereum each, amid the absence of specific legal regulation concerning NFTs in Indonesia. Employing a normative juridical approach, the study analyzes the potential recognition of NFTs within the secured transactions framework. Preliminary findings suggest that NFTs qualify as objects and are eligible for collateralization under Government Regulation No. 24 of 2022, although their application requires further comprehensive legal development and reform.